The Impact of Digitalization on the Efficiency of Investment Activity in the Main Sectors of the Ukrainian Economy - Kushnerenko Serhii M. (Bìznes Inform)
Digitalization is a key factor in the development of economies around the world. The intensive use of digital technologies is spreading both among households and in production. The aim of the article is to analyze the impact of digitalization on investment activity in the sectors of the Ukrainian economy and the formation of instruments for managing the impacts of digitalization. The article analyzes the prerequisites for the impact of digitalization on investment activity. It is emphasized that the features of the socioeconomic and socio-political system affect the transfer of digital technologies to high-tech production and exportation. It is noted that the level of digitalization implementation differs by sector of the economy – the greatest use of big data technologies is observed in the sectors of technology, healthcare and financial services, while industry and trade are less covered. Instruments for managing the impacts of digitalization on the efficiency of investment activity in the main sectors of the Ukrainian economy have been formed. The key role of analyzing the current state of digitalization, determining such key indicators as Internet penetration, the level of automation and the use of cloud technologies is noted, and a comparison of these indicators in accordance with international rankings is carried out. It is important to define the key sectors of the economy that have the greatest impact on GDP and employment, and assess the potential for attracting investment in each of these sectors. The role of partnerships between public, private and social organizations to work together on digitalization projects and develop communication strategies to inform the society and business about the benefits of digitalization is emphasized. The article may be useful for analysts, researchers, business associations, State and local authorities. Further research in this area will focus on the issue of quantitative assessment of the impact of digitalization on investment activities in various sectors of the Ukrainian economy.